Analysis of structural damage and maintenance needs in a coffin building: Case study in Jaboatão dos Guararapes-PE - Saruhashi, Mariana Lissa; Silva, Rayssa Valéria da; Lucena, Sabrina Rayane Silva; Monteiro, Eliana Cristina Barreto; Valério, Bianca Maria Vasconcelos (Technical and Scientific Journal Green Cities, 2024)
The article analyzes the structural damage and maintenance needs of a coffin building in Jaboatão dos Guararapes-PE, highlighting the importance of preserving the integrity of buildings with pathological manifestations. In order to create damage maps, a visual and color map was executed, with the purpose of identifying and mapping the anomalies that could compromise the durability of the building’s structure, highlighting the need for effective maintenance and restoration strategies. The methodology involved photographic analysis, the construction of damage maps using specific software and visual inspections. The results revealed that the pathological manifestations most commonly found on the building’s façades were the presence of vegetation, peeling and dirt. In addition, the north façade, being more protected from the sun and humidity, showed fewer points of dirt compared to the other façades. The areas of the façades most affected were identified and the need for immediate corrective maintenance of the building was noted. In conclusion, the damage map proved to be of great importance in helping to make appropriate decisions in the intervention process, with a view to preserving the structural and architectural integrity of the buildings affected, as well as guaranteeing sustainability in the field of construction.